Hybrid energy system as driver of sustainable rural development: An optimization and impact analysis of Tulefa Energy Village, Ethiopia - Sufyan Yakubu; Tsegaye Sissay Tedla; Sidique Gawusu; Samuel Dodobatia Wetajega; Mugisho Mugaruka Josue; Nasiru Alhassan; Getachew Adam Workneh (Energy Nexus)
In this study, we investigated the design and optimization of a hybrid energy system for Tulefa Energy Village in Ethiopia using the HOMER software. The village is off-grid, with the majority relying on traditional biomass while facing huge energy challenges. The design and optimization consisted of solar photovoltaic, wind turbines, battery storage, and a diesel generator to deliver reliable and sustainable electricity. Four configurations were modelled and analyzed based on key parameters such as technical, economic, and environmental impacts. Among the analyzed configurations, the optimal system which consist of 35 kW solar photovoltaic, 5.1 kW wind turbine, 15 kW diesel generator and 91 kWh battery storage achieved renewable fraction of 98.8 % with a levelized cost of electricity of $0.05018/kWh, and a total net present cost of $68,363. Additionally, the system demonstrated minimal fuel consumption and greenhouse gas emissions, making it environmentally sustainable and economically viable. Sensitivity analysis was performed by changing variables such as discount rates, inflation rates, and fuel prices to assess the performance of the system. The results of this study indicate the potential of energy systems to drive rural development in Ethiopia by offering a scalable solution for off-grid communities. This adds to the international discourse on rural electrification, and therefore, to policies, engineering, and community development.